Microstructures of ternary Zn-A1-Mg and quaternary Zn-A1-Mg-x alloys and their corrosion behaviour as coating on galvanized steel substrate - Low, Hai Tat, 1989-, author 563202; Esah Hamzah, supervisor 179197; Fakulti Kejuruteraan Mekanikal 8081 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Sarjana Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2016